2015
DOI: 10.3390/vaccines3040850
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Virus-Like Particle Streptococcal Vaccine Candidate Using B-Cell Epitopes from the Proline-Rich Region of Pneumococcal Surface Protein A

Abstract: Alternatives to the well-established capsular polysaccharide-based vaccines against Streptococcus pneumoniae that circumvent limitations arising from limited serotype coverage and the emergence of resistance due to capsule switching (serotype replacement) are being widely pursued. Much attention is now focused on the development of recombinant subunit vaccines based on highly conserved pneumococcal surface proteins and virulence factors. A further step might involve focusing the host humoral immune response on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 46 publications
1
18
1
Order By: Relevance
“…Thus, we hypothesize that the molecular mechanisms of the C5P-induced immunogenicity enhancement might be different from the previously reported high immunogenicity of proline-rich epitopes because the epitopes were located within the protein [37,38] which was in contrast to our observation that the immune response increased only with the 5-pro attached at the C terminus of the protein. We also hypothesize that the 5-arg might have enhanced the entry of BPTI into the cells during the endocytosis/ phagocytosis process [39][40][41], which might have increased the immunogenicity [42] of BPTI.…”
Section: Short Peptide Tag: a Biotechnological Tool For Increasing Imcontrasting
confidence: 99%
“…Thus, we hypothesize that the molecular mechanisms of the C5P-induced immunogenicity enhancement might be different from the previously reported high immunogenicity of proline-rich epitopes because the epitopes were located within the protein [37,38] which was in contrast to our observation that the immune response increased only with the 5-pro attached at the C terminus of the protein. We also hypothesize that the 5-arg might have enhanced the entry of BPTI into the cells during the endocytosis/ phagocytosis process [39][40][41], which might have increased the immunogenicity [42] of BPTI.…”
Section: Short Peptide Tag: a Biotechnological Tool For Increasing Imcontrasting
confidence: 99%
“…This finding may reflect that the immune response against the simultaneous administration of these epitopes could have complementary or synergistic effects by targeting different stages of pneumococcal invasion (34). This hypothesis is in line with recent animal studies demonstrating that when VPPs or VPP-derived protein fragments are combined as a mixture or as a macromolecular complex, the overall protection against pneumococcal infection is increased significantly (23)(24)(25).…”
Section: Figsupporting
confidence: 87%
“…Our study revealed the in vitro functional potential of human antibodies targeting selected epitopes derived from CbpD, PhtD, PhtE, and ZmpB VPPs by OPKA and the in vivo potential of these epitopes to elongate significantly the survival of mice challenged with a lethal dose of virulent clinical pneumococcal serotype 3. Our findings contribute significantly to the development of serotype-independent pneumococcal vaccines, since to date only a few VPP peptide/protein fragments that could exhibit such promising immunological characteristics have been used as vaccine candidates (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Based on basic biophysical properties 60-90 monomers can self-assemble into a 20-25 nm particle that contains a lipid core and a surface decorated by antigens. SVLP function as repetitive antigen displays and are capable of inducing humoral responses in vaccinated animals [185,186].…”
Section: Rationally Designed Protein Nanovaccinesmentioning
confidence: 99%